Independence of Lateral and Differential Longitudinal Movement of Indoleactic Acid in Geotropically Stimulated Coleoptiles of Zea mays - Cane, Alan R. (1969)
The possible interdependence of the differential longitudinal, and the lateral movement of indoleacetic acid (IAA) in horizontal Zea coleoptile segments has been examined. The coleoptiles have been opened out into flat pieces of tissue and supplied apically with IAA-1-(14)C. Opened-out segments orientated so that all the cells correspond with those at the `bottom' of a normal horizontal coleoptile, transport more IAA basipetally than do segments in which all the cells are equivalent to those at the `top' of the horizontal coleoptile. In opened-out segments orientated so that all the cells are equivalent to those at the side of the horizontal coleoptile cylinder, there is no difference in the basipetal transport capacity of the upper and lower halves. This is so even if the tissue has been in the horizontal position for 90 min before being bisected into its upper and lower halves. In this `side' tissue, however, there is a polarized downward movement of IAA. At least 95% of the (14)C in both the upper and lower halves of the tissue is confined to the IAA molecule. In horizontal Zea coleoptiles the polarized lateral movement of IAA can therefore occur independently of the differential basipetal transport of IAA in the upper and lower halves of the organ.